THE PROBLEM OF ENSURING THE SAFETY OF VEHICLES IN BRAKING MODES - Otabayev N.I.; Odilov O.Z.; Ibrohimov O.N. (European Science Publishing, 2023)
In this article, taking into account the conditions on the roads of Uzbekistan, the work that needs to be done to ensure the safety of vehicles in braking modes is fully explained. The interaction between the elements of the "Car-Driver-Road-Pedestrian-Environment" system in the modes of simultaneous braking of vehicles, as well as new methods, tools and technologies for diagnosing the braking system using new information technologies considered development processes. Methods of increasing car safety in braking modes based on the developed scientific rules, new methods, technologies for preventing traffic accidents and diagnostics of motor vehicles are widely covered.
Keywords: car, road traffic accident, bicycle, driver.